Evolution of optical wireless communication for B5G/6G. (May 2022) - Wei, Zixian; Wang, Zhaoming; Zhang, Jianan; Li, Qian; Zhang, Junping; Fu, H.Y.
Abstract: The research on optical wireless communication (OWC) has been going on for more than two decades. Particularly, visible light communication (VLC), as a means of OWC combining communication with illumination, has been regarded as a promising indoor high-speed wireless approach for short-distance access. Recently, lightwave, millimeter-wave (mmWave), terahertz (THz) and other spectrum mediums are considered as potential candidates for beyond fifth-generation/sixth-generation (B5G/6G) mobile communication networks. On the basis of previous studies, this review focuses on revealing how the research of next-generation OWC technology should be carried out to meet the requirements of B5G/6G for practical deployment. The research, development and engineering transformation of the OWC systems are a paragon of interdisciplinary. It involves a wide discussion on how to build a high-speed, multi-user, full-duplex, white-light OWC system based on existing technologies by showing the innovations and trade-offs at various levels with material, device, air-interface technology, system and network architecture. The compatibility of OWC is emphasized and some advanced heterogeneous OWC systems are presented, which involves the combination or integration of various functions such as sensing, near-infrared (NIR) beam-steering, positioning and coexistence with radio frequency (RF) communication. Finally, several potential directions are pointed out for the actual engineering deployment in the B5G/6G era.